Teachers’ beliefs on creative writing in English language teaching in Norway - Elisabeth Sundt (Inland Norway University of Applied Sciences, 2023)
The use of creative writing in education has seen an upturn in the last decades due to increased knowledge about its area of use and application in the classroom. Whether or not this upturn is visible in the Norwegian VGS EFL classroom is questioned and investigated in this thesis. The teachers and their beliefs are the focus of this study. The empirical data is collected from the answers of 42 teachers in a questionnaire and in a group interview with two teachers, all teaching English in general studies in Norway. The findings show how the teachers use creative writing less than academic writing in their classrooms. This has much to do with their lack of knowledge about creative writing and how it is not applied with conscious focus on development of writing skills but is rather seen as a time-consuming task that is fun, but not integral to learning and developing writing skills. Researchers within the area has a different take on this, however, and sees how creative writing can aid the development of specific writing skills amongst others, and how creative writing is process rather than a product. This lack of knowledge amongst the teachers about creative writing as a tool for foreign language learning also limits its use and position in the classroom. The implications of this is less varied writing and a limited possibility to use of the language in different writing tasks, which is discussed in this thesis.